PENGARUH MANAJEMEN KARIR ORGANISASI DAN INDIVIDU TERHADAP KEPUASAN KARYAWAN SERTA IMPLIKASINYA TERHADAP KINERJA KARYAWAN PT. BIO FARMA (PERSERO) - Iskandar Iskandar (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2019)
ABSTRACTThis study examines the effect of organizational and individual career management to job satisfaction and implications for the performance of employees. The object of this research are employees of PT. Bio Farma, the state-owned company engaged in the pharmaceutical field. The populationof this study is 828 while the number of employees and the sample size is 90 people. Design of this research is descriptive and causal. Descriptive research is research that is designed to outline the characteristics of a population, causal research is research that has the main purpose to prove the causal connection or relationship affects and is affected of the variables studied. This study used path analysis (path analysis) that run through SPSS 22:00 in view ofthe effect between dependent and independent variables. These results indicate thatorganizational an individual career management positive and significant impact on jobsatisfaction, job satisfaction and a significant positive effect on performance, and organizations and individual career management positive and significant impact on employee performance. From the results of this study can be seen that in an effort to improve job satisfaction and employee performance it is necessary to pay attention to the provision of career information in the form of an opportunity to occupy a more open positions available to employees. In addition to improving employee satisfaction and employee performance tersbut need to plan his career so he can be the opportunity to be promoted in company.